2012
DOI: 10.1007/s10329-012-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of zoonoses derived from humans in captive chimpanzees

Abstract: Emerging infectious diseases (EIDs) in wildlife are major threats both to human health and to biodiversity conservation. An estimated 71.8 % of zoonotic EID events are caused by pathogens in wildlife and the incidence of such diseases is increasing significantly in humans. In addition, human diseases are starting to infect wildlife, especially non-human primates. The chimpanzee is an endangered species that is threatened by human activity such as deforestation, poaching, and human disease transmission. Recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…Three quarters of zoonotic EIDs are caused by pathogens in wildlife and the incidence of such diseases is increasing significantly in humans [1,2]. Human activities have contributed to a closer contact between humans and wildlife due to a complex relationship between social and environmental factors causing a major threat both to human health and biodiversity conservation mainly through disease transmission between the two groups [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Three quarters of zoonotic EIDs are caused by pathogens in wildlife and the incidence of such diseases is increasing significantly in humans [1,2]. Human activities have contributed to a closer contact between humans and wildlife due to a complex relationship between social and environmental factors causing a major threat both to human health and biodiversity conservation mainly through disease transmission between the two groups [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in African sanctuaries (Schaumburg et al 2012) and in a captive facility in Japan (Kooriyama et al 2013) has also documented human-associated pathogens in chimpanzees. In chimpanzee sanctuaries in Zambia and Uganda, Schaumberg et al (2012) found a high prevalence of drug-resistant human-associated Staphylococcus aureaus , and suggest that this may be due to treatment of individual apes with antibiotics or the close caregiver-chimpanzee contact required for rehabilitation of these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a widespread perception that human infectious diseases pose one of the greatest risks to the survival of apes in the wild (Homsy 1999; Leendertz et al 2006; Altizer et al 2007; Chi et al 2007; Pederson et al 2007; Köngden et al 2008;). Although confirming cross-species transfers of infectious agents from humans to wild non-human primates can be difficult, numerous suspected and/or confirmed transmission events have been documented in the wild (Nizeyi et al 2001; Köndgen et al 2008; Rwego et al 2008) and in captive settings (Schaumburg et al 2012; Kooriyama et al 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 71.8% of zoonotic events occurring in humans can be traced to wildlife (43), including AIDS, avian flu, plague, foot and mouth disease, rabies, and dengue fever. Wildlife resources are very abundant in China where more than 5,300 types of vertebrates live (44).…”
Section: Health Problems In Chinamentioning
confidence: 99%